2009
DOI: 10.1097/ccm.0b013e3181b6ed58
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis-associated encephalopathy and its differential diagnosis

Abstract: Sepsis is often complicated by an acute and reversible deterioration of mental status, which is associated with increased mortality and is consistent with delirium but can also be revealed by a focal neurologic sign. Sepsis-associated encephalopathy is accompanied by abnormalities of electroencephalogram and somatosensory-evoked potentials, increased in biomarkers of brain injury (i.e., neuron-specific enolase, S-100 beta-protein) and, frequently, by neuroradiological abnormalities, notably leukoencephalopathy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
166
0
12

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 229 publications
(181 citation statements)
references
References 56 publications
3
166
0
12
Order By: Relevance
“…Brain dysfunction in sepsis may involve a number of alternative mechanisms, which have been reviewed extensively elsewhere (Papadopoulos et al, 2000;Ebersoldt et al, 2007;Iacobone et al, 2009), and will only briefly be outlined here. These mechanisms and the six principal components of the oxidativenitrosative stress cascade proposed above are not mutually exclusive, and may to different extents interact to affect brain function in sepsis.…”
Section: Complementary Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Brain dysfunction in sepsis may involve a number of alternative mechanisms, which have been reviewed extensively elsewhere (Papadopoulos et al, 2000;Ebersoldt et al, 2007;Iacobone et al, 2009), and will only briefly be outlined here. These mechanisms and the six principal components of the oxidativenitrosative stress cascade proposed above are not mutually exclusive, and may to different extents interact to affect brain function in sepsis.…”
Section: Complementary Mechanismsmentioning
confidence: 99%
“…In the latter setting, organ dysfunction, including acute brain dysfunction, termed sepsis-associated encephalopathy (SAE) or sepsis-associated delirium, occurs in up to two thirds of patients (Vincent et al, 2006). SAE may be the first symptom of sepsis, and is characterized by confusion, agitation, and impaired consciousness (Young et al, 1990;Bolton et al, 1993;Ebersoldt et al, 2007, Iacobone et al, 2009). These symptoms may be an independent predictor of death (Sprung et al, 1990;Ebersoldt et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Encephalopathy in the setting of sepsis is often associated with neurophysiologic and neuroradiologic abnormalities and is likely multifactorial in etiology. 22 A study of septic children demonstrated background patterns on EEG consistent with moderate to severe encephalopathy and elevated serum S100 beta and neuron-specific enolase compared to controls, indicating that neurologic injury may occur with sepsis. 23 A study of adults in a medical intensive care unit reported that about one-third of patients with sepsis had electrographic seizures or periodic epileptiform discharges and the presence of sepsis was the only predictor of electrographic seizures or periodic epileptiform discharges.…”
mentioning
confidence: 99%
“…Drug-related permanent brain damage is well documented in SAE and the coexistence of SS is likely to be a factor in a worsening prognosis. 20 …”
Section: Clinical Implications For the Surgeonmentioning
confidence: 99%